Comparative Immunomodulatory Activity of Methanolic Extract obtained from Tabernaemontana alternifolia Leaves and Stem: Immunomodulatory Effects of Methanolic Extracts from Tabernaemontana alternifolia Leaves and Stem - Karanje, Pallavi; Vishwajeet Ghorpade,; Ajay Namdeo,; Sawale, Jyotiram; Namdeo Jadhav,; Jotsana Gandhi,; Rohan Phatak,; Abhijit Karanje, (Iranian Journal of Pharmaceutical Sciences, 2025)
Tabernaemontana alternifolia, a plant of the Apocynaceae family and commonly referred to as Kampillakah, is a medicinal plant recognized for its remarkable therapeutic benefits. The plant stems, roots, and leaves are abundant in alkaloids, which have been traditionally used to treat cancer, diarrhea, and syphilis. Due to bioactive alkaloids and phenolic compounds, the current study aimed to evaluate the immunomodulatory effects of methanolic extracts from Tabernaemontana alternifolia leaves (TAL). It stems (TAS) in mitigating cyclophosphamide-induced myelosuppression in rats. Preliminary phytochemical analyses revealed the presence of compounds known for immunomodulatory properties. The administration of these extracts resulted in a notable recovery of hemoglobin levels and red and white blood cell and platelet counts, with TAL demonstrating greater effectiveness compared to TAS. Body weight measurements corroborated the protective effects, such as TAL and TAS significantly increased rat body weight during treatment. Furthermore, TAL and TAS enhanced neutrophil adhesion, an important marker of immune system activation. Overall, the results indicate that TAL, in particular, offers notable immunomodulatory benefits that may help mitigate the adverse effects of chemotherapy-induced myelosuppression and boost immunity against infections, delineating its potential for therapeutic use in integrative medicine.